(untitled) (Journal of the Management Sciences, 2025)
Poor road conditions, high transport costs and distant markets have been identified as factors that hamper improved market access for emerging farmers in rural areas. Infrastructure imparts welfare such utility derivable from existing and budgeted income, productivity and capacity to earn income and household and also national stock real wealth in the rural and urban economies. Inadequate or low quality infrastructure has serious implication for welfare and persistence of poverty. The study therefore sought; to examines the correlation between rural road transport infrastructure and farmers’ income in Osun State farm settlement. A cross sectional survey research design was used for the study. The primary data were obtained through administration of structured questionnaires for the farmers in Osun state farm settlement. The purposive sampling method was used to select (354) three hundred and fifty-four rural farmers from all the nine farm settlements in Osun State. Descriptive and inferential statistics such as frequencies, tables and Pearson product moment correlation coefficient used to test the relationship between existing rural road transportation infrastructure and farmers’ income. Results revealed a significant positive relationship between road access conditions and farmers’ annual income (r = 0.579, p < 0.05). The study concluded that rural road transport infrastructure has significant relationship on farmers ‘income in the studied area. Furthermore, the study recommends that government should address farmers to rural market services which are in bundles, and policies targeted towards rural infrastructural development most especially rural roads should be formulated because bulk of farm produce comes from the rural areas.